Gypsy from the Oriental: Bajo Ethnic in the Sulawesi Sea - Asba, Abdul Rasyid; Ali, Ismail (TAWARIKH, 2014)
ABSTRACT: The Bajo is a greatest maritime community in Indonesia archipelago. The community is not only known as a nomad tribe upon the boat, but as an ethnic without settlement habit geographically. However, her existence as an ethnic cannot be denied, especially from socio-cultural aspect. It is caused by a fact that the Bajo ethnic has a language, custom, trust system, kinship, and cultural values as basic for her social live. In maritime world of Indonesia, as a link that related to political and economic powers in Nusantara, the Bajoâs role and existence cannot be ignored. Her function even is equated with another maritime ethnic such as Bugis, Makassar, Buton, Mandar, and Malays. The main difference to another groups is her cultural exclusive, namely the Bajo ethnic did not play a crucial role in a culture spread as Islamization. The Bajo did not have an active role in the establishment of political control by ruling elite, locally as well as regionally. Her living that limited to her role as fisher and supplier of maritime products for economically traditional and domestic markets confers a special character for the community. Her apathy toward political polarization and her refusal to participate in domestic political constellation motivates her to avoid any reason to open conflict. This attitude makes the Bajo to be known as a loving-peace group with her subsistence and conflict avoiding. With her nomad live style, the Bajo can be termed as a subsistence Gypsy from the Oriental. KEY WORDS: Bajo ethnic, maritime community, nomad tribe, fisher and supplier of maritime products, loving-peace group, and Gypsy from the Oriental.Â Â Â About the Authors: Prof. Dr. Abdul Rasyid Asba is a Lecturer at the History Department, Faculty of Humanities UNHAS (Hasanuddin University) in Makassar, South Sulawesi, Indonesia; and Assoc. Prof. Dr. Ismail Ali is a Lecturer at the History Program, School of Social Sciences UMS (Malaysia University of Sabah) in Kota Kinabalu, Malaysia. They can be reached via e-mails at: rasbawecu@yahoo.com and ismailrc@ums.edu.myHow to cite this article? Asba, Abdul Rasyid & Ismail Ali. (2014). âGypsy from the Oriental: Bajo Ethnic in the Sulawesi Seaâ in TAWARIKH: International Journal for Historical Studies, Vol.6(1) October, pp.25-34. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (September 2, 2014); Revised (October 2, 2014); and Published (October 28, 2014).